2017
DOI: 10.3390/v9110342
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Homologous End Joining Protein PAXX Acts to Restrict HSV-1 Infection

Abstract: Herpes simplex virus 1 (HSV-1) has extensive interactions with the host DNA damage response (DDR) machinery that can be either detrimental or beneficial to the virus. Proteins in the homologous recombination pathway are known to be required for efficient replication of the viral genome, while different members of the classical non-homologous end-joining (c-NHEJ) pathway have opposing effects on HSV-1 infection. Here, we have investigated the role of the recently-discovered c-NHEJ component, PAXX (Paralogue of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Therefore, we think that herpesviruses also need to block NHEJ in favor of HR in order to achieve the loss of recircularization of their genomes. It was demonstrated that the NHEJ protein PAXX acts as a restriction factor for HSV-1 replication [65]. PAXX interacts with Ku80 and gets relocated after HSV-1 infection, and depletion of PAXX has been shown to enhance HSV-1 replication [65].…”
Section: Dna Damage Response Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we think that herpesviruses also need to block NHEJ in favor of HR in order to achieve the loss of recircularization of their genomes. It was demonstrated that the NHEJ protein PAXX acts as a restriction factor for HSV-1 replication [65]. PAXX interacts with Ku80 and gets relocated after HSV-1 infection, and depletion of PAXX has been shown to enhance HSV-1 replication [65].…”
Section: Dna Damage Response Proteinsmentioning
confidence: 99%
“…It was demonstrated that the NHEJ protein PAXX acts as a restriction factor for HSV-1 replication [65]. PAXX interacts with Ku80 and gets relocated after HSV-1 infection, and depletion of PAXX has been shown to enhance HSV-1 replication [65]. For KSHV, the depletion of Ku80 and DNA-PK, two proteins involved in NHEJ, leads to enhanced genome replication [56].…”
Section: Dna Damage Response Proteinsmentioning
confidence: 99%
“…Many components of the antiviral DDR pathways are degraded or inhibited by viral infection (reviewed in (Smith and Weller, 2015)). These include proteins involved in classic nonhomologous end joining (Lees-Miller et al, 1996;Parkinson et al, 1999;Trigg et al, 2017), homologous recombination signaling (Lilley et al, 2010), and ATR signaling involved in single strand DNA break repair (Mohni et al, 2010). Sensing of damaged DNA by the DDR system can detect the foreign DNA (especially open-ended DNA containing nicks and gaps) and may initiate a cascade of events to prevent viral gene expression before replication initiates (Lilley et al, 2011).…”
Section: Dna Damage Responsementioning
confidence: 99%
“…Co-immunoprecipitation experiments have shown that the interaction of Ku80 with Zta can be mapped to the region associated with DNA binding and dimerization, between amino acids 168 and 245 of Zta. [16], XRCC4 [17], Ku70 [20] Epstein Barr virus EBV Ku80 [24], DNA-PKcs [29] Herpes simplex virus 1 HSV-1 DNA-PKcs [10,34,37,39], Ku80 [38], Ku70 [39], Lig4/ XRCC4 [40], PAXX [42],…”
Section: Epstein Barr Virusmentioning
confidence: 99%
“…Although PAXX-knockout cells have an intact immune response, the virus seems to have a reproductive advantage and greater numbers of infectious virions are produced than in wild type cells. The authors suggest that PAXX acts to reduce the viral fitness by sequestering viral DNA in the cell leading to a reduced release of fully infectious HSV-1 particles [42].…”
Section: Introductionmentioning
confidence: 99%